The effects of nanoporous Fe2O3 synthesized via mechano-thermal process on electrical and optical properties of zinc oxide - Guler, Seval Hale; Boyrazli, Mustafa; Basgoz, Oykum; Yakuphanoğlu, Fahrettin (Elsevier, 2018)
This study was performed to investigate the effects of nanoporous hematite (Fe2O3) the electrical and optical properties on zinc oxide. Zinc oxide powder was commercially obtained. The nanoporous hematite with iron core was prepared using a specific method including ball milling and annealing processes. The particle size of the nanoporous hematite was determined to be 40-50 nm using an electron microscope. The electrical conductivity values of pure ZnO and the composites with 1% Fe2O3, 3% Fe2O3, and 5% Fe2O3 were obtained to be 6.55x10(-5), 5.35x10(-4), 3.79x10(-4) and 1.29x10(-4) S/cm, respectively. The nanoporous Fe2O3 with iron core increases the electrical conductivity of the ZnO-nanoporous: Fe2O3 composites. The optical band gap (E-g) values of the composites were determined by the Kubelka-Munk theory based on the diffused reflectance. As the nanoporous Fe2O3 content is increased, the Eg values of the composites are decreased. The obtained results indicate that the electrical and optical properties of the ZnO semiconductor is improved with the nanoporous Fe2O3.
Keywords: Nanocomposite; ZnO; Nanoporous Fe2O3; Optical properties; Electrical properties